Kemampuan Literasi Numerasi Berdasarkan Kecerdasan Logis Matematis Melalui Soal AKM Pada Siswa SMP - Diah Shela Andrianti; Puji Rahayu (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2022)
Abstract Numeracy literacy skills are skills in to use several types of numbers and symbols related to mathematics in analyzing, interpreting, and applying the information that has been obtained to solve problems in everyday life. This study aims to determine numeracy literacy skills based on mathematical logical intelligence through AKM questions for junior high school students. This research is a descriptive research with a qualitative approach. Data collection techniques were in the form of logical-mathematical intelligence questionnaires as research subjects, numeracy literacy tests in the form of AKM questions and interviews with selected subjects. The results of this study indicate that students in the high category are able to use knowledge, interpret problems with formulas, write down steps and strategies, use complex and complicated models to solve situations correctly, use reasoning on problems but are not correct. Whereas students in the moderate category are able to use knowledge, interpret problems with formulas, write down steps and strategies, use models to solve complex and complicated situations but are incorrect, use reasoning on questions but are incorrect. For students in the low category, they are able to use knowledge, interpret problems but are incorrect, have not written down steps and strategies, have not used models to solve complex and complicated situations, use reasoning but are incorrect.